Occipital blood‐brain barrier permeability is an independent predictor of visual outcome in type 2 diabetes, irrespective of the retinal barrier: A longitudinal study. (23rd January 2018) - Abuhaiba, S. I.; Cordeiro, M.; Amorim, A.; Cruz, Â.; Quendera, B.; Ferreira, C.; Ribeiro, L.; Bernardes, R.; Castelo‐Branco, M.
Abstract: Blood‐brain barrier (BBB) permeability in type 2 diabetic patients has been previously shown to be altered in certain brain regions such as the basal ganglia and the hippocampus. Because of the histological and functional similarities between the BBB) and the blood‐retinal barrier (BRB), we aimed to investigate how the permeability of both barriers predicts visual outcome. We included 2 control groups (acute unilateral stroke patients, n = 9; type 2 diabetics without BRB leakage n = 10) and a case study group of type 2 diabetics with established BRB leakage (n = 17). We evaluated sex, age, disease duration, metabolic impairment, retinopathy grade and BBB permeability as predictors of visual acuity at baseline, 12  and 24 months in the type 2 diabetics without BRB leakage group and the case study group. We have also explored differences in BBB permeability in the occipital lobe and frontal lobe in the 3 different groups. K trans (volume transfer coefficient) and V p (fractional plasma volume) were estimated. The BBB permeability parameter V p was higher in the case study group compared to the unaffected hemisphere of the stroke patient control group, suggesting vascular dynamics were changed in the occipital lobe of type 2 diabetics with established BRB leakage. These patients showed a significant correlation between glycated hemoglobin (HbA1C) levels and occipital and frontal K trans . We report for the first time that occipital BBB permeability is an independent predictor of visual acuity at baseline, as well as at 12 and 24 months, in type 2 diabetics with established BRB leakage. Our results suggest that occipital BBB permeability might be an independent biomarker for visual impairment in patients with established BRB leakage.